Public Fundraising Campaign By Migrant Care For Liberation of Migrant Worker Satinah From Death Penalty In Saudi Arabia - Nadya Husein Zainuddin; AG Eka Wenats Wuryanta (COMMENTATE: Journal of Communication Management, 2021)
Fundraising is not a common thing anymore. Especially if the fundraising is about the social campaign that will attract people’s sympathy. Fundraising that Migrant Care did as one of the most successful public fundraising. Migrant Care had successfully collected 2,8 billion rupiahs in 2 weeks. This fundraising is for Satinah, an Indonesian migrant worker who was sentenced do death penalty because she was charged with murdering her employer. Migrant Care is non-governmental organization which protect the rights of Indonesian migrant workers stated their disappointment towards the Indonesian government that didn’t help Satinah. Because of their disappointment, Migrant Care held the crowdfunding for Satinah’s diyat. The method that used in this research is qualitative descriptive with interview and documentation with Carl Hovland’s theory SMCR (source, message, channel and receiver).